A UX model for the evaluation of learners' experience on lms platforms over time - Mkpojiogu, Emmanuel O. C. (2022)
Although user experience (UX) is dynamic and evolves over time, prior research reported that the learners' experience models developed so far were only for the static evaluation of learners' experiences. So far, no model has been developed for the dynamic summative evaluation of the UX of LMS platforms over time. The objective of this study is to build a UX model that will be used to evaluate learners' experience on LMS over time. The study reviewed relevant literature with the goal of conceptualizing a theoretical model. The Stimuli-Organism-Response (SOR) framework was deployed to model the experience engineering process. To verify the model, 6 UX experts were involved. The model was also validated using a quasi-experimental design involving 900 students. The evaluation was conducted in four time points, once a week for four weeks. From the review, a conceptual UX model was developed for the evaluation of learners' experience with LMS design over time. The outcome of the model verification shows that the experts agreed that the model is adequate for the evaluation of learners' experience on LMS. The results of the model validation indicate that the model was highly statistically significant over time (Week 1: x2(276) = 273 I 9.339, Week2: x2(276) = 23419.626, Week3: x2(276) =18941.900, Week4: x2(276) = 27580.397, p=000<0.01). Each design quality had strong positive effects on the learners' cognitive, sensorimotor and affective states respectively. Furthermore, each of the three organismic states: cognitive, sensorimotor, and affective, had strong positive influence on learners' overall learning experience. These results imply that the experience engineering process was successful. The study fills a significant gap in knowledge by contributing a novel UX model for the evaluation of learners' experience on LMS platforms over time. UX quality assurance practitioners can also utilize the model in the verification and validation of learner experience over time